Guinea : Eighth and Final Review Under the Extended Credit Facility Arrangement and Financing Assurances Review, and Request for Extension of the Current Arrangement-Press Release; and Staff Report. - International Monetary Fund. African Dept. (Washington, D.C. : International Monetary Fund, 2016)
This paper discusses Guinea's Eighth and Final Review Under the Extended Credit Facility (ECF) Arrangement and Financing Assurances Review, and Request for Extension of the Current Arrangement. Guinea's medium-term economic prospects are good. Growth is projected to average 5 percent during 2017-20, on the back of higher investments in the mining sector, increases in food production, and better electricity services. The recovery in the agricultural sector will allow the growth rebound to be shared by larger segments of the population, but the sector remains vulnerable to weather-related supply shocks. The IMF staff supports the completion of the eighth review under the ECF arrangement and financing assurances review.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet